Seasonal and intra-seasonal variations of suspended-sediment distribution in the Yellow Sea. (15th September 2017) - Zang, Zhengchen; Xue, Z. George; Bi, Naishuang; Yao, Zhigang; Wu, Xiao; Ge, Qian; Wang, Houjie
Abstract: Seasonal and intra-seasonal variability of hydrodynamics and suspended sediment concentration (SSC) in the Yellow Sea were investigated using combined ship measurements and physical fields extracted from the global Hybrid Coordinate Ocean Model (HyCOM). Model-data comparison indicates that the HyCOM solutions fairly agree with the observed temperature fields, both showing strong horizontal and vertical seasonality. High SSC was observed in waters near the Chengshantou Cape and above the old Yellow River subaqueous delta in November 2012, and was coincident with enhanced velocity shear. Thermal fronts were identified in waters less than 60 m deep with their prominent appearances in November 2012, inhibiting the offshore sediment transport. The previously reported depo-center of distal Yellow River mud-patch off the Chengshantou Cape was confined between the positions of the strong velocity shear in a shoreward direction and the thermal fronts in an offshore direction. We concluded that the nearshore mixing front and the offshore thermal front play critical roles in both capture of the fine-grained suspended sediment and formation of the Omega-shaped mud patch. Highlights: We present the seasonal and intra-seasonal distributions of SSC in the Yellow Sea. HyCOM solutions fairly agree with observations on seasonal variability of temperature. High SSC in the coast of Yellow Sea was coincident with enhanced velocity shear. Thermal fronts in shallow water constrained the offshore sediment transport.